Answer:
$289 I think
Step-by-step explanation:
$289 I think
sorry if I am wrong
Answer:
2:1???
Step-by-step explanation:
Answer:
(23, 4)
Step-by-step explanation:
If we use substitution, we need to rewrite the 2nd equation so we can substitute it into the first.
Step 1: Rewrite 2nd equation
x = 5y + 3
Step 2: Substitution
2(5y + 3) - 5y = 26
Step 3: Distribute
10y + 6 - 5y = 26
Step 4: Combine like terms
5y + 6 = 26
Step 5: Isolate <em>y</em>
5y = 20
y = 4
Step 6: Find <em>x</em>
x - 5(4) = 3
x - 20 = 3
x = 23
And we have our final answer!
Answer:
y = 7x - 4
just as it says in words